Penolakan Konsep Time Value of Money dalam Ekonomi Islam untuk Menjaga Pertumbuhan Ekonomi Tetap Produktif - Asnaini, Asnaini; B, Idwal; Yuningsih, Ayu (Fakultas Syariah IAIN Kerinci, 2023)
This study aims to reveal that the concept of time value of money in Islamic economics is as a rejection of the practice of interest (usury) or economics that ignores the real sector. The study used qualitative methods of content analysis with secondary data. The results revealed that Islamic economics rejects the concept of time value of money. Money is money, not a commodity. Money should always be positioned as a medium of exchange regardless of changes or additional time. Time cannot be the cause for the increase in the value of money in the past that exists in the present. Additions that are allowed are additional because of both business and social transactions. Additions due to loan contracts that position money as a commodity are strictly prohibited (haram) because they lead to interest (usury) instead of profit (profit). If this happens, it will seriously endanger economic growth. The economy became uncompetitive and the principles in Islamic economics were not fulfilled.